Central Bank Governance and Reserve Portfolios Investment Policies : An Empirical Analysis - Klingebiel, Daniela; Herrero Montes, Carmen Mileva; Ruiz, Marco; Seward, James (World Bank, Washington, DC, 2021)
This paper uses a unique survey data set of 105 central banks to investigate whether investment policies for central bank foreign reserve portfolios are linked to the governance arrangements for reserve management. The paper evaluates whether a central bank's investment decision-making structure impacts how much risk institutions take in their reserve management operations and the level of diversity in their reserve portfolios. Additionally, it explores the implications of the broader governance environment on reserve management. The analysis yields four key findings. First, internal governance arrangements matter for foreign reserve portfolio investment policy; the empirical results indicate that reserve portfolios are more diversified in central banks in which the middle office directly reports to the board. Second, controlling for the level of reserves, the macroenvironment, and the broader governance environment, reserve portfolios are more diversified in central banks where the back, middle, and front offices are separated. Third, the regression analysis also reveals that central banks in countries where the Ministry of Finance has an obligation to cover negative equity have fewer eligible currencies and are therefore less diversified. Fourth, central banks where boards actively exercise portfolio oversight usually have portfolios with more risk and diversification. Portfolios with longer investment horizons, more currencies, and a broader set of asset classes have performed better historically while limiting downside risk. Given that the analysis controls the broader governance environment, the data indicate that any central bank can improve its internal governance regardless of the external governance environment. This paper contributes to the literature on central bank foreign reserves management and on understanding the importance of governance arrangements in investment policy.